Biology Education for Social and Sustainable Development
XXII, 406 p.
Keywords: In an era of globalization and urbanization, various social, economic, and environmental challenges surround advances in modern biological sciences. Considering how biological knowledge and practice are intrinsically related to building a sustainable relationship between nature and human society, the roles of biology education need to be rethought to respond to issues and changes to life in this biocentury. This book is a compilation of selected papers from the Twenty Third Biennial Conference of the Asian Association for Biology Education 2010. The title, Biology Education for Social and Sustainable Development, demonstrates how rethinking and reconstruction of biology education in the Asia-Pacific region are increasingly grounded in deep understandings of what counts as valuable local knowledge, practices, culture, and ideologies for national and global issues, and education for sustainable development. The 42 papers by eminent science educators from Australia, China, Philippines, Singapore, Taiwan, and the U.S., represent a diversity of views, understandings, and practices in biology education for sustainable development from school to university in diverse education systems and social-cultural settings in the Asia-Pacific region and beyond. The book is an invaluable resource and essential reference for researchers and educators on Asian perspectives and practices on biology education for social and sustainable development.